2022
DOI: 10.3390/molecules27020568
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Insecticidal Activities of Essential Oils against the Pulse Beetle

Abstract: Pulse beetles, Callosobruchus chinensis and Callosobruchus maculatus, are essential pests of cowpea, gram, soybean and pulses. Application of synthetic insecticides against the pulse beetle has led to insect resistance; insecticide residues on grains affect human health and the environment. Essential oils (EOs) are the best alternatives to synthetics due to their safety to the environment and health. The main objective of the investigation was to study the chemical composition and insecticidal activities of EO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
(57 reference statements)
4
9
0
Order By: Relevance
“…In the present study, the EO of A. maritima showed 84–96% repellence and ovipositional deterrence (OD 50 = 3.30–4.01 mg/L) against C. chinensis and C. maculatus . The present results are similar to the earlier studies, where EOs of M. spicata , M. piperita , and T. minuta showed 84 to 96% repellency [ 4 ]. In another study, the EO of Ocimum gratissimum exhibited 73–93% repellence against C. chinensis after 24 h [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In the present study, the EO of A. maritima showed 84–96% repellence and ovipositional deterrence (OD 50 = 3.30–4.01 mg/L) against C. chinensis and C. maculatus . The present results are similar to the earlier studies, where EOs of M. spicata , M. piperita , and T. minuta showed 84 to 96% repellency [ 4 ]. In another study, the EO of Ocimum gratissimum exhibited 73–93% repellence against C. chinensis after 24 h [ 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…In a related study, A. dracunculus , A. santonicum , and A. spicigera (5 μL/L air) showed 88–95% mortality [ 21 ] and A. sieberi showed promising fumigant toxicity (LC 50 = 1.45 μL/L air) against C. maculutus [ 24 ]. Similarly, the EOs of Mentha spicata , M. piperita , and Tagetes minuta showed promising fumigant toxicity against adults of C. chinensis (LC 50 = 0.9–1.4 µL/mL) and C. maculatus (LC 50 = 1.1 to 2.0 µL/mL) [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several plant-derived essential oils of Acorus calamus, Aegle marmelos, Cedrus deodara, Mentha piperita, Mentha spicata, Murraya koenigii, and Tagetus minuta were reported to have insecticidal activities against various insect pests in previous studies (Reddy et al, 2016;Jayaram et al, 2022a). Additionally, the homogeneous or heterogeneous blends of essential oils also revealed that the insecticidal activities against various species of mealybugs, including Pseudococcus calceolariae (Tacoli et al, 2018), Planococcus citri (Cloyd et al, 2009;Erdemir and Erler, 2017), Planococcus ficus (Karamaouna et al, 2013;Peschiutta et al, 2017;Tacoli et al, 2018;Brahmi et al, 2022), Pseudococcus longispinus (Hollingsworth and Hamnett, 2009;Tacoli et al, 2018), Paracoccus marginatus (Mwanauta et al, 2021), Planococcus minor (Prabowo and Damaiyani, 2019), Phenacoccus solenopsis (Mostafa et al, 2018;Saad et al, 2021), and Pseudococcus viburni (Ramzi et al, 2017) have been reported earlier.…”
Section: Introductionmentioning
confidence: 99%